Information and telecommunication system of pre-trial investigation: international experience and ways of implementation - H. I. Hlobenko (Bulletin of Kharkiv National University of Internal Affairs)
The purpose of the article is to study the institute of pre-trial investigation and prospects for its further improvement by converting into electronic format. According to the goal, the research aims to develop a position on creating the most optimal model of information and telecommunication system of pre-trial investigation, as well as to study the prospects of its implementation and identify possible issues that may arise during pre-trial investigation in electronic format.